2017
DOI: 10.1002/sono.12104
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal sonography: Sonographer reflections on patient experience using a critical incident technique

Abstract: Introduction: It is important to understand patient experiences of transvaginal sonography (TVS) due to its intimate nature and potential for patient discomfort. This may place the sonographer at increased risk of complaints and litigation due to misunderstandings and unfulfilled patient expectations.Methods: The critical incident technique was used to elicit the personal experiences of sonographers performing TVS to provide perspectives of sonographer practices and their perceptions of patient experiences. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…34 Not knowing what to expect from an imaging examination can increase patient anxiety. 35 There were similar findings in our study: “I find a lot of my patients are very stressed, because they don’t know what’s going on” (PS28) and “you get someone to sign a consent form but they still don’t really understand” (PS16). However, in each instance the examination still proceeded.…”
Section: Resultssupporting
confidence: 78%
“…34 Not knowing what to expect from an imaging examination can increase patient anxiety. 35 There were similar findings in our study: “I find a lot of my patients are very stressed, because they don’t know what’s going on” (PS28) and “you get someone to sign a consent form but they still don’t really understand” (PS16). However, in each instance the examination still proceeded.…”
Section: Resultssupporting
confidence: 78%
“…31 It is crucial that the referring doctor provides a complete explanation to allow patients appropriate time to consider what is involved, especially for more intimate examinations. 26 However, several prior studies conducted outside Australia have concluded that referring doctors are not providing adequate information to their patients due to an incomplete understanding of medical imaging and the involvement of ionising radiation. 5,13,19,20 This could result in the patient consenting to a procedure without being fully informed.…”
Section: Discussionmentioning
confidence: 99%
“…5,13,19,20 This could result in the patient consenting to a procedure without being fully informed. 11,26 Referring doctors' knowledge of ultrasound imaging, specifically the examination procedure and risks, needs to be assessed in an Australian setting to determine if patients are receiving adequate and accurate information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation